Intergenerational Poverty Dynamics in Poland: Family Background and Children's Educational Attainment During Transition - Charlotte Lauer; Miriam Beblo (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
In this paper, we analyse the intergenerational transmission of poverty from Polish parents to their children through childrens educational attainment during the transition process of the 1990s. The relationship between family background and education is investigated using an ordered probit model of educational attainment with data from the Polish Labour Force Survey. The results show that childrens education is strongly related to household structure, parents education, city size, and region of residence. Household income and the parents labour market situation have only a weak, though significant, effect on childrens education. We conclude that, if poverty transmission takes place between generations, this seems to be primarily caused by the inheritance of human capital rather than by pure wealth effects.
Keywords: P36; I21; 330; Educational Decisions; Transition; Armut; Generationenbeziehungen; Übergangswirtschaft; Familiensoziologie; Bildungsniveau; Schätzung; Polen